ANALISIS KONTRASTIF KATA SAPAAN/PANGGILAN DALAM KELUARGA PADA MASYARAKAT LAMPUNG DIALEK A/O - Saputra, Dira; Firnanda, M. Evan; Prayogi, Rahmat; Riadi, Bambang (FKIP Universitas Lampung, 2024)
This study aims to analyze and explain the function of various greeting words or calls in kinship relations, especially in families in the Lampung community, both in the A/O dialect. This study uses a quantitative approach method. Data analysis used contrastive analysis, namely comparing the similarities and differences of the two languages. The data were obtained from the results of filling out a questionnaire conducted by students of the Lampung Language Education study program at the University of Lampung. The results of the study show that there is a great diversity of greeting words in the midst of the people of Lampung from various regions. This variation of greeting words experiences a balance in the Lampung language, both from dialect A and dialect O. Penelitian ini bertujuan untuk menganalisis dan menjelaskan fungsi ragam kata sapaan atau panggilan dalam hubungan kekerabatan terutama dalam keluarga yang ada di masyarakat Lampung baik dialek A/O. Penelitian ini menggunakan metode pendekatan kuantitatif. Analisis data menggunakan analisis kontrastif yaitu membandingkan persamaan dan perbedaan dua bahasa yang sama. Data diperoleh dari hasil pengisian kuisioner yang dilakukan oleh mahasiswa program studi Pendidikan Bahasa Lampung di Universitas Lampung. Hasil penelitian menunjukkan banyaknya keberagaman kata sapaan yang ada ditengah masyarakat Lampung dari berbagai daerah. Variasi kata sapaan ini mengalami keseimbangan dalam Bahasa Lampung baik dari dialek A maupun dialek O.